460. Point-of-Care, In-Home SARS-CoV-2 IgG Antibody Testing to Assess Seroprevalence in At-Risk Health Care Workers. (31st December 2020) - Meissner, Eric G; Litwin, Christine; Crocker, Tricia; Mack, Elizabeth; Card, Lauren
Abstract: Background: Health care workers are at significant risk for infection with the novel coronavirus SARS-CoV-2. Methods: We utilized a point-of-care, lateral flow SARS-CoV-2 IgG immunoassay (RayBiotech) to conduct a seroprevalence study in a cohort of at-risk health care workers (n=339) and normal-risk controls (n=100) employed at an academic medical center. To minimize exposure risk while conducting the study, consents were performed electronically, tests were mailed and then self-administered at home using finger stick blood, and subjects uploaded a picture of the test result while answering an electronic questionnaire. We also validated the assay using de-identified serum samples from patients with PCR-proven SARS-CoV-2 infection. Results: Between April 14 th and May 6 th 2020, 439 subjects were enrolled. Subjects were 68% female, 93% white, and most were physicians (38%) and nurses (27%). In addition, 37% had at least 1 respiratory symptom in the prior month, 34% had cared for a patient with known SARS-CoV-2 infection, 57% and 23% were worried about exposure at work or in the community, respectively, and 5 reported prior documented SARS-CoV-2 infection. On initial testing, 3 subjects had a positive IgG test, 336 had a negative test, and 87 had an inconclusive result. Of those with an inconclusive result who conducted a repeat test (85%), 96% had a negative result. All 3 positive IgG tests were in subjects reporting prior documented infection. Laboratory validation showed that of those with PCR-proven infection more than 13 days prior, 23/30 were IgG positive (76% sensitivity), whereas 1/26 with a negative prior PCR test were seropositive (95% specificity). Repeat longitudinal serologic testing every 30 days for up to 4 times is currently in progress. Conclusion: We conducted a contact-free study in the setting of a pandemic to assess SARS-CoV-2 seroprevalence in an at-risk group of health care workers. The only subjects found to be IgG positive were those with prior documented infection, even though a substantial proportion of subjects reported significant potential occupational or community exposure and symptoms that were potentially compatible with SARS-COV-2 infection. Disclosures: All Authors : No reported disclosures